Spontaneous coronary artery dissection of the proximal left circumflex artery: a case report. Issue 3 (6th July 2019) - Pineda, Aleksandra; Martin, Josh; Puri, Aniket; Jahangiri, Bijan
Abstract: Background: Spontaneous coronary artery dissection (SCAD) has gained attention as an important cause of acute coronary syndrome and sudden cardiac death (SCD) among women. Management strategies of SCAD differ from those of atherosclerotic disease. There is an elevated risk of complications and suboptimal outcomes in patients with SCAD undergoing percutaneous coronary interventions (PCIs). Case summary: A 48-year-old woman without any traditional cardiovascular risk factors was admitted with severe central chest pain with associated dyspnoea and diaphoresis. The patient had a strong family history of SCD, affecting three female members in their 40s and 50s. Cardiac troponins were elevated. Coronary angiogram showed moderate to severe stenosis of the proximal circumflex coronary artery. Optical coherence tomography confirmed SCAD with sub-intimal haematoma. Despite significant stenosis in the proximal segment of a relatively large artery, a decision was made not to proceed with PCI. The follow-up angiogram demonstrated normal coronaries. Magnetic resonance imaging of renal arteries showed features suggestive of fibromuscular dysplasia affecting the right renal artery. Subsequent genetic counselling and gene testing were unremarkable. Discussion: Conservative management of SCAD is recommended because the large majority of SCAD lesions heal naturally, whereas PCI is associated with increased risk of complications and adverse outcomes. Whether SCAD is associated with the sudden death events in our patient's family remains unclear. It certainly raises concerns as to an inheritable condition. In the absence of post-mortem findings in her family members, we can only speculate about this representing a possible inheritable form of SCAD.